Prevalence and correlates of metabolic syndrome in the adolescents of Rural Wardha - Vijay Bhalavi; Pradeep R Deshmukh; Kalyan Goswami; Neelam Garg (Wolters Kluwer Medknow Publications, 2015)
Background and Objective: Metabolic syndrome is a major concern as a precursor of cardiometabolic diseases. The present study was designed to study the magnitude and correlates of metabolic syndrome among the adolescents of rural Wardha. Materials and Methods: A cross-sectional study was carried out among the adolescents (10-19 years) of Anji PHC. A sample of 405 was selected by random sampling from the sampling frame available with department of Community Medicine. We collected data about their sociodemographic variables and other cardiometabolic risk factors. Fasting blood sample was collected to measure lipid profile and blood glucose. Blood pressure and anthropometric measurements (height, weight, and waist circumference) were also taken. Results: Prevalence of metabolic syndrome using ATP-III criteria modified for adolescents was found to be 9.9% (95% CI: 7.3-13.1) in the study population and lower level of high-density lipoprotein (HDL) cholesterol was found with a prevalence of 58.3% (95% CI: 53.4-63.0). The prevalence of metabolic syndrome was found to be significantly (P < 0.05) associated with the presence of obesity and hypertension among family members. Interpretation: There was a moderately high prevalence of metabolic syndrome among rural adolescents. Conclusion: The early identification of cardiometabolic risk factors such as hypertension and obesity can help prevent metabolic syndrome, diabetes, and cardiovascular disease.